Enzymatic Specific Production and Chemical Functionalization of Phenylpropanone Platform Monomers from Lignin. Issue 2 (16th December 2016) - Ohta, Yukari; Hasegawa, Ryoichi; Kurosawa, Kanako; Maeda, Allyn H.; Koizumi, Toshio; Nishimura, Hiroshi; Okada, Hitomi; Qu, Chen; Saito, Kaori; Watanabe, Takashi; Hatada, Yuji
Abstract: Enzymatic catalysis is an ecofriendly strategy for the production of high‐value low‐molecular‐weight aromatic compounds from lignin. Although well‐definable aromatic monomers have been obtained from synthetic lignin‐model dimers, enzymatic‐selective synthesis of platform monomers from natural lignin has not been accomplished. In this study, we successfully achieved highly specific synthesis of aromatic monomers with a phenylpropane structure directly from natural lignin using a cascade reaction of β‐O‐4‐cleaving bacterial enzymes in one pot. Guaiacylhydroxylpropanone (GHP) and the GHP/syringylhydroxylpropanone (SHP) mixture are exclusive monomers from lignin isolated from softwood ( Cryptomeria japonica ) and hardwood ( Eucalyptus globulus ). The intermediate products in the enzymatic reactions show the capacity to accommodate highly heterologous substrates at the substrate‐binding sites of the enzymes. To demonstrate the applicability of GHP as a platform chemical for bio‐based industries, we chemically generate value‐added GHP derivatives for bio‐based polymers. Together with these chemical conversions for the valorization of lignin‐derived phenylpropanone monomers, the specific and enzymatic production of the monomers directly from natural lignin is expected to provide a new stream in "white biotechnology" for sustainable biorefineries. Abstract : Enzymatic cleavage of lignin : Marine bacterial enzymes recognize and cleave various lignin substructures near β‐O‐4 linkages and produce two phenylpropanones selectively. These monomers are promising platforms for producing bioplastics and other functional chemicals in medical and cosmetic industries. This study provides a new stream for "white biotechnology".